Design and evaluation of a hybrid energy system for Masirah Island in Oman. Issue 4 (3rd July 2020) - Abdul-Wahab, Sabah Ahmed; Charabi, Yassine; Al-Mahruqi, Abdul Majeed; Osman, Isra
ABSTRACT: This paper discusses the possibility of replacing or supplementing Masirah Island's current diesel generation system with a hybrid energy system consisting of solar photovoltaics (PV), a wind turbine and a natural gas generator to meet the island's growing electricity demand. Hybrid Optimisation Model for Electric Renewables (HOMER) modelling software uses input data, including costs, resource data, technology components, and load data, to simulate a hybrid system. The list of options, ordered according to the system's net present cost (NPC), is generated by the software. The results of the simulation identified the optimal option, which would be a combination of the wind turbine, natural gas, and diesel generators. This option gave the lowest NPC of 129 million and a cost of energy (COE) of 0.0724 /kWh. This COE of the optimal hybrid energy system was very low compared to the COE of the current diesel system (0.302 /kWh). It also resulted in a lower pollutant emission compared to the current diesel power system. Implementing a hybrid renewable energy system would ensure a low COE and less pollution for the island.